High-performance single-layer polymer electrophosphorescent devices with polymer oxides - Chen, Fang-Chung; Chien, Shang-Chieh; Lee, Shih-Wei (My University, 2008)
An enhanced power efficiency and a lower driving voltage of polymer electrophosphorescent devices have been demonstrated by blending poly(ethylene glycol) (PEG) into the active layer. The luminance efficiency of the device with Al cathode was up to 15.6 cd/A and the turn-on voltage was decreased to 5.6 V after the use of PEG. Further, the power efficiency was also improved to 5.0 lm/W. Moreover, similar improvement was also observed while Ca/Al or LiF/Ca/Al were used as the cathodes. The performance enhancement can be attributed to the interaction between Al and organic molecules with ethylene oxide groups, resulting in a better contact. (c) 2008 The Electrochemical Society.